Implications of prostate inflammation on male fertility - Motrich, Rubén D. (2018)
Fil: Motrich, Rubén D. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Departamento de Bioquímica Clínica, Argentina.